Work Goals of Asian Managers: Contrasting Evidence to the Meaning of Working Study - Pearson, C.; Chatterjee, Samir (2004)
Following the seminal study by George England and his Meaning of Working (MOW) research team (MOW, 1987), which assessed managerial perceptions of the relative importance of a set of 11 work goals, a stream of follow-up research has been undertaken over the past twenty years. With the recent forces of convergence of managerial work goals unleashed by the logic of globalization, it has become relevant to extend these investigations to social contexts where managerial values and assumptions have been different from the contexts of the MOW study. The macro-level economic reform and progress in Asian societies are mostly mediated by the values and goals of managers at the micro-level setting, and, therefore, the replication of the MOW study in these societies has considerable relevance. This paper documents the relative importance of a set of 11 work goals for a sample of 2057 managers in eight Asian nations. The study reveals that as the Asian national environments move forward with divergent reform agenda, there is a convergence emerging in the work goal priorities. These converging findings contrast sharply with the previous MOW findings. The paper provides an analysis and discussion on this outcome.